2021
DOI: 10.2337/db20-1081
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell Expression and Release of Kidney Injury Molecule-1 in Response to Glucose Variations Initiates Kidney Injury in Early Diabetes

Abstract: Half of the mortality in diabetes is seen in individuals <50 years of age and commonly predicted by the early onset of diabetic kidney disease (DKD). In type 1 diabetes, increased urinary albumin-to-creatinine ratio (uACR) during adolescence defines this risk, but the pathological factors responsible remain unknown. We postulated that early in diabetes, glucose variations contribute to kidney injury molecule-1 (KIM-1) release from circulating T cells, elevating uACR and DKD risk. DKD risk was assigned i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…HAVCR1 is a costimulatory molecule expressed on the surface of immune cells, which promotes activation and proliferation of immune cells, cytokine secretion and regulates the immune response ( Guo et al, 2019 ; Evans and Liu, 2020 ; Xiao et al, 2020 ). In this regard, HAVCR1 can alter the function of CD8 + T cells and NK cells for an effective antitumor immune response ( Lee et al, 2010 ; Forbes et al, 2021 ). An increasing body of evidence suggests that the positive and negative regulation of HAVCR1 by ligand-binding is essential for maintaining immune homeostasis ( Xiao et al, 2007 ; Brooks et al, 2015 ; Du et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…HAVCR1 is a costimulatory molecule expressed on the surface of immune cells, which promotes activation and proliferation of immune cells, cytokine secretion and regulates the immune response ( Guo et al, 2019 ; Evans and Liu, 2020 ; Xiao et al, 2020 ). In this regard, HAVCR1 can alter the function of CD8 + T cells and NK cells for an effective antitumor immune response ( Lee et al, 2010 ; Forbes et al, 2021 ). An increasing body of evidence suggests that the positive and negative regulation of HAVCR1 by ligand-binding is essential for maintaining immune homeostasis ( Xiao et al, 2007 ; Brooks et al, 2015 ; Du et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Glycemic changes increase KIM-1 production from CD8 + T cells, thus raising the risk of DKD in patients with diabetes. 68 Increased numbers of peripheral blood CD4 + CR5 + PD-1 + THF cells were also found in patients with DKD, 69 and patients with type 2 diabetes and proteinuria express more CD25 and CD69 on their circulating CD8 + T cells. 70 Moreover, the serum levels of T-lymphocyte activation markers, specifically CD28 and CTLA-4, increase as DKD progresses.…”
Section: Role Of Immune Cells In Dkdmentioning
confidence: 96%
“…KIM-1 is also known as T-cell lg mucin 1 (TIM-1) or hepatitis A virus cellular receptor 1 and has been reported as a transmembrane glycoprotein receptor on T cells ( 120 ). Recent studies have revealed elevations in KIM-1, suggesting that glycemic variations may increase the production of KIM-1 in CD8 + T cells in individuals with DKD, thereby increasing the risk of DKD ( 121 ). The elevations in circulating KIM-1 also increases the urinary KIM-1 in DN, verifying that KIM-1 can be a biomarker and a reliable predictor of diabetic kidney injury ( 122 ).…”
Section: Recruitment and Activation Of T Cells In Diabetic Kidney Dis...mentioning
confidence: 99%